E-KOMUNIKOWANIE PUBLICZNE W WARUNKACH PANDEMII COVID-19 – DOŚWIADCZENIA MAŁYCH MIAST DOLNEGO ŚLĄSKA - Glinka, Kamil (Polityka i Społeczeństwo, 2021)
The aim of the article is to analyze the process of public e-communication in the so-called first wave of the COVID-19 pandemic, i.e., between March and August 2020. The selection of the studied cases – seventy-two small towns in the Lower Silesian Voivodeship – allows for the following hypothesis: there is a certain model of public e-communication about the COVID-19 pandemic based on specific: (1) institutional and legal solutions; (2) instruments; (3) thematic threads. The use of several different, though complementary, research methods (comparative analysis, content analysis, questionnaire) leads to the conclusion that the hypothesis can be confirmed only partially. It turns out that the process of e-communication between small towns and the internal environment (inhabitants) is based on certain truncated "components", which does not change the fact that these towns also perceive the need to exchange content (in the form of text, graphics, audio or video) on the nature of the COVID-19 pandemic and related changes and limitations.